Reducing greenhouse gas emissions via harvest residue management in eucalyptus afforestation on Brazilian sandy soils - Freitas Brilhante de São José, Jackson; Lisboa, Bruno Britto; Vieira, Frederico Costa Beber; Zanatta, Josiléia Acordi; Araujo, Elias Frank; Martins, Juscilaine Gomes; Bender, Andressa Classer; Carniel, Eduardo; Bayer, Cimelio; Vargas, Luciano Kayser (Frontiers in Plant Science, 2025)
IntroductionThe greenhouse gas balance is a central theme in discussions related to forest ecosystems. In this context, the present study evaluated the impact of five eucalyptus harvest residue management systems on atmospheric C-CO2 retention in soil, greenhouse gas (GHG) emissions, and the global warming potential (GWP) in Eucalyptus saligna plantations.MethodsThe management systems examined were: AR - all harvest residues retained on soil; NB - harvest residues kept on soil, except bark; NBr - harvest residues kept on soil, except branches; NR - all harvest residues (bark, branches, leaves) removed; NRs - all residues from the previous rotation and new plantation litter removed using shade cloth. Soil emissions of nitrous oxide (N2O) and methane (CH4) were monitored over 12 months (October 2016 to October 2017). Soil samples were collected to a depth of one meter to assess atmospheric C-CO2 retention. Results and discussionAnnual N2O emissions were low (0.11–0.23 kg N-N2O ha−1 year−1) and showed no clear relationship with the amount of nitrogen added through residues. The soil consistently functioned as a methane sink across all management systems, with CH4 fluxes ranging from –2.56 to –3.91 kg C-CH4 ha−1 year−1. The highest rate of C-CO2 retention in soil (–5,540 kg C-CO2 ha−1 year−1) was observed under the AR management system, while the lowest (–1,752 kg C-CO2 ha−1 year−1) occurred under the NRs system. AR management also resulted in the lowest global warming potential (–33,946 kg C-CO2 ha−1 year−1), primarily due to soil C-CO2 retention (15.43%) and carbon accumulation in biomass and wood products (84.57%). These findings demonstrate that retaining eucalyptus harvest residues in subtropical sandy soils, in conjunction with carbon sequestration in wood products, constitutes an effective forest management strategy for mitigating global warming.